(untitled) (Journal of the College of Basic Education, 2022)
Many researchers dealt with failure distribution models and their different applications in the field of reliability and life tests. In this research, the measurement parameter and the reliability function will be estimated for one of the Rayliegh Failure Distributions, and focus on the comparison between some methods of estimating the measurement parameter and the reliability of the distribution for complete data and first-type control data. . An experimental study was conducted using simulation and giving different values ​​for the parameter  and different sample sizes (n = 10,25,50,100). The experiment was repeated (Rp = 500 times) to obtain great homogeneity between the estimates. All simulation and comparison results will be summarized in special tables prepared for this purpose.